2019
DOI: 10.1007/s11899-019-00546-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Personalized Treatment of Patients with Chronic Myeloid Leukemia

Abstract: Purpose of Review Treatment goals and ambitions have even been upwardly revised since demonstration was made that under certain conditions, treatment-free remission was possible. Herein, we will discuss on how to try tailoring treatment choices to the unique characteristics of each patient. Recent Findings Since the first-generation ATP-competitive TKI imatinib was made available in the clinic in 2001, secondgeneration drugs such as dasatinib, nilotinib and bosutinib and the third-generation TKI ponatinib have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In this context, TKI dose reduction strategies represent significant opportunities at all stages of treatment to prevent and manage severe adverse events or to improve patients' adherence to the medication. This approach could also be of importance for patients in sustained DMR, either as maintenance therapy or as a prelude to successful TFR 5,6 . On this subject, we and other authors have shown that a low‐dose TKI policy could be applied safely and efficiently in patients with CML who respond optimally to treatment 7,22,30 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this context, TKI dose reduction strategies represent significant opportunities at all stages of treatment to prevent and manage severe adverse events or to improve patients' adherence to the medication. This approach could also be of importance for patients in sustained DMR, either as maintenance therapy or as a prelude to successful TFR 5,6 . On this subject, we and other authors have shown that a low‐dose TKI policy could be applied safely and efficiently in patients with CML who respond optimally to treatment 7,22,30 .…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the achievement of TKI discontinuation with prolonged treatment‐free remission (TFR) has become a new therapeutic goal in CML 4 . In addition to the strategy of stopping TKI therapy, reducing the dose of the targeted drug used for maintenance therapy can also be considered for patients in optimal response to prevent adverse side effects and to improve quality of life 5,6 . However, this approach has been underappreciated in the context of clinical trials 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a survival rate of 88.3% after 10 years of imatinib treatment has been reported in [ 7 ]. In addition, the availability of second- (dasatinib, nilotinib) and third-generation tyrosine kinase inhibitors (bosutinib, ponatinib) further improves therapy efficacy and provides additional targeted treatment strategies to overcome resistance against imatinib [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the excellent treatment responses to available targeted treatment strategies, a development from the chronic phase to the blast crisis is only rarely observed today [ 6 , 10 ]. Nevertheless, in some cases CML is still first diagnosed at the stage of blast crisis [ 11 , 12 , 13 ] and in other cases the gain of additional mutations can lead to treatment failure and CML progression [ 8 ]. Unfortunately, high and long-term response rates to targeted tyrosine kinase inhibitors are mainly achieved for the chronic phase, but such treatments are less efficient in accelerated phase or blast crisis [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, imatinib and nilotinib have a good safety profile, although the finding of grade 1/2 non-hematological side effects is quite common. 8 , 9 Nausea, vomiting, diarrhea, fluid retention, fatigue, and muscle spasm are the most prevalent side effects of imatinib treatment 10 , whereas nilotinib treatment frequently results in an increase in cardiovascular events, particularly QT prolongation, and a skin rash. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%